Never boring classics: 100 historians in the optics of iconography [Review: Russian Historians. Iconography. 4 Books. Chernobaev A.A. (Ed.). Moscow, Sobranie, 2008–2019. (In Russian)] - V.P. Korzun (Ученые записки Казанского университета: Серия Гуманитарные науки)
The review presents reflections on four books “Russian Historians. Iconography” compiled and edited by A.A. Chernobaev. The books were published in 2008–2019. They described 100 historians in the optics of iconography. V.N. Tatishchev opens the iconographic range, while I.V. Tunkina completes it, for the moment. The structure of the iconographic “texts” is unified. First, a short biographical sketch of one page is given, which is followed by 14–15 pages of engravings (lithographs), photographs with signatures and dating. A short bibliography (the main works published by the historian and the literature about them) is included in the special section of each book. The four-volume edition was analyzed as a complex metahistoriographic text. Its appearance and construction was considered in the mainstream of modern biography and visual turn. Personal motives, appeals of A.A. Chernobaev to this project, and its connection with the experience of the “Historical Archive” journal, in which photographic documents have been actively published since 2000, were studied. The focus of attention was also the scientific program of the project, in which three main areas of research/presentation are distinguished: to visually present three centuries of Russian historiography development; to reflect the disciplinary mosaic of historical science in persons; to present portraits of metropolitan and provincial historians. At the same time, some difficulties in the implementation of this program were indicated. They are associated both with the unevenness of the surviving visual sources and with the insufficient development of the problems of classicalization in modern historiography. The presented iconography significantly expands the scope of the scientist’s formalized questionnaire, which is reflected in a short biographical text (basic biographical data: social origin, education, scientific biography with the inclusion of master’s/candidate’s and doctoral dissertations, career path, list of major works). As a result, the classics of historiography appear not as monuments, but as living people. The visual range clearly highlights the cultural stylistics of various generations of historians.